What environmental and climatic factors influence multidecadal fire frequency? - David Lindenmayer; Chris Taylor; Wade Blanchard; Phil Zylstra; Maldwyn John Evans (Ecosphere, 2023)
Abstract Fire is a key ecosystem process with more than half the world's land surface potentially subject to fire. A key aspect of fire ecology is the fire regime, with fire frequency an important component. Fire frequency appears to be increasing in some ecosystems, but decreasing in others. Such temporal and spatial variability in fire frequency highlights the importance of more effectively quantifying spatiotemporal changes in fire frequency for particular environments. We modeled changes in fire frequency over the past 40 years (1981–2020) in a 4.64 million ha area in Victoria, Australia. We quantified regional variation in the number of fires (hereafter termed fire frequency) during two 20‐year time periods (1981–2000 vs. 2001–2020), employing the Interim Biogeographic Regionalisation for Australia (IBRA), a standardized regionalization of Australia's terrestrial landscapes. We also quantified the climate and environmental factors influencing fire frequency in each IBRA subregion. Our empirical analyses revealed that fire frequency in Victoria was heterogeneous in both time and space. Wildfire frequency changed between 1981 and 2020, with the past 20 years (2001–2020) experiencing a substantially greater number of fires relative to the 20 years prior (1981–2000). Changes in fire frequency were not spatially uniform, with increases more pronounced in some IBRA subregions than others. Climate and topographic factors influenced the frequency of wildfires, but their effects manifested differently in different IBRA subregions. For example, fire frequency was associated with increasing rainfall deficit deviation in four IBRA subregions, but an opposite trend characterized two others. Associations between fire frequency and increasing temperature deviation also varied from negative to positive across subregions. We also found evidence of elevation, slope, and aspect effects, but these too varied between IBRA subregions. The complex spatiotemporal changes in fire frequency quantified in this study, and the complex between‐region differences in the factors associated with the number of fires, have major implications for biodiversity conservation, resource availability (e.g., timber yields), and ecosystem integrity. In ecosystems subjected to repeated fires at short intervals, new rapid detection and swift suppression technologies may be required to reduce the risks of ecosystem collapse as high‐severity wildfires increase in frequency.